SENAM LANSIA DENGAN DIAGNOSA HIPERTENSI PADA NY. K DI DESA KARANGGAMBAS - Anggiriana Trie Utama; Eko Sari Ajiningtyas; Wiwik Priyatin (Jurnal Ilmiah Medsains, 2023)
Cases of hypertension in people aged ≥18 years who had high blood pressure measured at the Padamara Health Center were 14.55% in 2014. Decreased to 2.44% in 2015 and rose again to 9.02% in 2016. From the data obtained at the Gerbus Gymnastics Community for the Elderly, in Karanggambas Vilage, Padamara District, Purbalingga Regency, ≥10 ederly people are affeceted by hypertension. This study aims to determine the exercise of the elderly with a diagnosis of hypertension in Karanggambas Vilage, Padamara District, Purbalingga Regency. Case study design is something that is very important in research. Case study subjects to be addressed for research by researchers. The focus of the case study is the first study of the problem that will serve as the point of reference for the case study. Operational definition of the variables formulated. Case study instruments are conducted by examining cases to provide in-depth understanding. Menthods of data collection process approach to the characteristics of the subjets needed in a study. Location and time of case study. Data analysis and presentation. The results show that for 3 times in 3 weeks, nursing care has been carried out by doing elderly exercise with effective hypertension sufferers in the elderly, obtained data on a decrease in blood pressure. Blood pressure data before and after doing eldery exercise 160/80-138/82 MmHg. From this case study, it can be seen that giving elderly gymnastics can reduce high blood pressure in elderly people with the main problem of ineffective peripheral perfusion.